The relationship between hygiene factors of herzberg theory and job satisfaction among non-executive employees in Royal Malaysian Customs Department (JKDM), Kuching, Sarawak/ Natalie Deester Melchior - Deester Melchior, Natalie (2016)
Nowadays, organizations may face many challenges in order to satisfy their employees, especially those who are non-executive employees to cope with organization changes to achieve success and goals for the organization. The organization must satisfy the employees need in order to increase efficiency among them, and to increase to job commitment and motivation in doing their work by taking salary, supervision, and work environment in consideration. The purpose of this study was to investigate the relationship between the hygiene factors of HerzbergTheory and Job Satisfaction among non-executive employees in Royal Malaysian Customs Department (JKDM), Kuching, Sarawak. There were three hygiene factors of Herzberg Theory used in this study which consisted salary, supervision and work environment. These three hygiene factors were tested to see the relationship with job satisfaction. This study used quantitative method. The data was collected through questionnaire. The questionnaire was adopted and adapted from previous study questionnaire by Paul E. Spector (1985). The targeted population was non-executive employees. The number of respondents from which the data have been collected was 80 out of 86 sample sizes. The data collection method used was questionnaire. The results of this study indicates that the main hygiene factor of Herzberg Theory that contribute to the job satisfaction among non-executive employees is work environment (M=3.75, SD=0.69241). It is vital for the organization to motivate their employees to work hard in order to achieve the organization goals and objectives.